2022
DOI: 10.1039/d2tb01360f
|View full text |Cite
|
Sign up to set email alerts
|

Probing the alignment-dependent mechanical behaviors and time-evolutional aligning process of collagen scaffolds

Abstract: Efficiently manipulating and reproducing the collagen (COL) alignment in vitro remains challenging because many of the fundamental mechanisms underlying and guiding the alignment process are not known. We reconcile experiments...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…In comparison to the blank and grass carp group, quantitative results revealed that the migration ratio reached the peak under cross‐link (10%), while the migration behaviors decreased when the EDC/NHS cross‐link concentration reached to 50% or 100% (Figure 3D). Previous reports demonstrated that cross‐link could regulate the mechanical properties of collagen, [ 23 ] and stiffness favors the migration of cells. [ 24 ] Then we speculated that the migration behavior in the cross‐link condition (Figure 3D) was mainly controlled by these two factors.…”
Section: Resultsmentioning
confidence: 99%
“…In comparison to the blank and grass carp group, quantitative results revealed that the migration ratio reached the peak under cross‐link (10%), while the migration behaviors decreased when the EDC/NHS cross‐link concentration reached to 50% or 100% (Figure 3D). Previous reports demonstrated that cross‐link could regulate the mechanical properties of collagen, [ 23 ] and stiffness favors the migration of cells. [ 24 ] Then we speculated that the migration behavior in the cross‐link condition (Figure 3D) was mainly controlled by these two factors.…”
Section: Resultsmentioning
confidence: 99%